Analisis Yuridis Implementasi Kebijakan Pengelolaan Sampah di Kabupaten Sukoharjo Berdasarkan Peraturan Daerah Nomor 16 Tahun 2011 - Triyas Nuraini; Nides Fransisca Marshanda; Mutiara Devita Putri; Alya Maya Khonsa Rahayu (Lembaga Pengembangan Kinerja Dosen, 2026)
This research intends to legally examine how waste management policies are applied in Sukoharjo Regency according to Regional Regulation Number 16 of 2011. The main problem identified in this study is the gap between well-defined legal standards and their actual implementation in practice at the field level. This study uses a normative legal research approach with statutory and conceptual methods, supported by secondary data obtained through library research from relevant legal literature and documents. The findings show that, from a normative perspective, the legal structure for waste management in Sukoharjo Regency is comprehensive and already incorporates modern principles of environmental law, including waste reduction, proper waste management, and the implementation of the 3R principles (Reduce, Reuse, Recycle). However, in practice, the implementation is not yet fully effective as expected. This is caused by several influencing factors such as low levels of public environmental awareness, inadequate supporting infrastructure, and weak enforcement of existing regulations by relevant authorities. This condition clearly reflects a gap between das sollen (what should be) and das sein (what is happening in reality) in the execution of waste management policy. Overall, the study emphasizes that stronger implementation efforts are needed to bridge the gap between legal norms and practical outcomes in environmental governance.